THE EFFECT OF LEAF AREA INDEX CHANGES ON LAND SURFACE TEMPERATURE IN WEST KALIMANTAN - Aprilina Aprilina; Riza Adriat; Laras Toersilowati (International Journal of Remote Sensing and Earth Sciences, 2024)
West Kalimantan, located along the equator, is a tropical area with high surface temperatures. Decreasing forests or green spaces in this region could endanger the creatures living there, due to rising surface temperatures. Hence, analyzing the impact of Leaf Area Index changes on soil surface temperature is vital. This research employed remote sensing technology via the Terra-MODIS satellite to analyze this impact. The satellite imagery was used to determine Leaf Area Index (LAI) and Land Surface Temperature (LST), using image data from 2001 and 2021 in West Kalimantan Province. The research revealed that the region underwent changes, with wide pine forests being replaced by savanna land. The surface temperature value with the largest distribution area remained between 25ᵒC to 30ᵒC in both 2001 and 2021. LAI changes affected LST by 46% to 47%, but substantial changes require a significant number of years to observe.